2011 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--18723
|View full text |Cite
|
Sign up to set email alerts
|

Student Satisfaction with ASEE Activities and its Impact on ASEE Student Membership

Abstract: Columbia and has been employed-by or affliated with ABB Inc. since 2003. His most recent role with ABB was as a Group North American Account and Marketing Manager for the Power Products Division Transformer Business Unit. Prior to this Dan was with ABB High Voltage Products circuit breaker service and ABB utility front end sales organizations. Before joining ABB, Dan was with the sears.com web center team as a communication and product specialist. Dan received his Ph. D. in industrial engineering from the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…A motivated faculty advisor can be a strong leader in the recruitment of student members of a professional organization. The American Society for Engineering Education surveyed a cross-section of its student members and found that 62% of their student members learned about the ASEE from a professor or an advisor [8]. While this was a survey of all ASEE student members, not just those affiliated with a student chapter, we can reasonably project that professors and specifically the student chapter faculty advisor is in a position to introduce many students to the professional organization and its student chapter.…”
Section: Success Factorsmentioning
confidence: 96%
“…A motivated faculty advisor can be a strong leader in the recruitment of student members of a professional organization. The American Society for Engineering Education surveyed a cross-section of its student members and found that 62% of their student members learned about the ASEE from a professor or an advisor [8]. While this was a survey of all ASEE student members, not just those affiliated with a student chapter, we can reasonably project that professors and specifically the student chapter faculty advisor is in a position to introduce many students to the professional organization and its student chapter.…”
Section: Success Factorsmentioning
confidence: 96%
“…A Likert scale instrument was developed for surveyed members to rank their satisfaction on ASEE events, from which a significant conclusion can be drawn, "it can be inferred that events of interest to the SCC, i.e., those in which the SCC was involved in the planning and executing, scored higher than other eventsaverage of 3.28. It is also of importance to note that nearly 20 percent of the respondents have never attended a single ASEE event" [11]. Also of note is the lawnmower exercise used by the US Naval Academy-a week-long immersive exercise designed to build demonstrable technical skills in structures and materials, thermo-fluid sciences, and engineering design; with the corollary goal of promoting confidence and kinesthetic learning in the students who were tasked with disassembling, reassembling, and analyzing the operation of the familiar machine.…”
Section: Background Researchmentioning
confidence: 99%